Removal of boron from industrial wastewater by chitosan via chemical precipitation - Abu Hassan, Mohd. Ariffin; Lim, Soo Hui; Noor, Zainura Zainon (Faculty of Chemical and Natural Resources Engineering,Universiti Teknologi Malaysia, 2009)

(untitled)
Chitosan is natural organic polyelectrolytes of high molecular weight and charge density; obtained from deacetylation of chitin. This study explored the potential and effectiveness of applying chitosan as a primary coagulant and flocculent for boron removal. A series of batch coagulation and flocculation processes with chitosan under different conditions, i.e. dosage, pH and temperature were conducted, in order to determine the optimum operating conditions for boron removal. The performance was accessed through total suspended solids (TSS), turbidity and boron concentration reductions. From the study, the optimum dosage for chitosan was recorded at 0.8 g/L with 94.2%, 91% and 79.7% for TSS, turbidity and boron, respectively. The optimum pH of 5 with the removal of TSS, turbidity and boron concentration were 97.8%, 93.4% and 87.5%, respectively. At the temperature of 60C, the reduction of all the parameters (i.e. TSS, turbidity and boron concentration) was the highest compared to other temperature (i.e. 99%, 95.3% and 91% of TSS, turbidity and boron concentration reductions were achieved respectively)